EVALUASI RISIKO TI PT. KLM MENGGUNAKAN COBIT 5.0 DOMAIN APO12 - Septia Angelika Gettin Daely; Chintia Cantika; Agnes Elsye Permata Sari; Sri Andayani (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
This study assesses IT risk management capability at PT. KLM using COBIT 5.0 APO12. Current capability (As-Is) is level 3 (Established Process), with consistent but incomplete documentation and integration, while target capability (To-Be) is level 5 (Optimising Process). The gap highlights the need for better documentation, monitoring, data integration, and automated evaluation. Recommendations include formal process documentation, standardized risk matrices, clear unit roles, and periodic reviews to achieve more effective risk management aligned with strategic objectives.